Induced defecation in honeybees - Grunander, Mattias (2015)
Growing human populations and technological achievements in later years, have increased interactions between people, and made the world smaller. Diseases travel around the globe at an ever increasing speed. There is a growing need to develop an epidemiological model, so that outbreaks and transmission routes can be predicted. Aspects such as genetics, social networks and random contact must be investigated and incorporated, if the model is to fit human populations. Humans would be the preferred test subject, but for practical and ethical reasons, it is not feasible. It is therefore necessary to conduct the experiments on another social animal group. Honeybees are social insects, living in complex societies. Older foragers collect pollen and nectar from flowers, and younger nurse bees ingest the pollen grains in order to feed the foragers, drones and the queen. There are different levels of genetic relativeness amongst bees, since the queen mate with multiple drones. The bees interact more with their closely related kin than with other bees from the same hive. Observing disease transmission between bees by analyzing bee feces is a method that has not yet been properly studied. It is in this project assumed that disease transmission of pathogens can be detected, by investigations of the bee feces. To acquire feces from an individual bee is difficult, so means of feces collection from the bees must be developed. Induced defecation by centrifugation is one method in which the bees are centrifuged at a high speed for a short period of time. Centrifuged bees were put in cages, in order to determine whether the centrifuging process affected their long-term survival. The negative side with centrifugation is that it puts the bee in risk of losing its intestines and die. By using the centrifuge, bees suffer from intestine loss at a relatively low speed, 2000 RPM upwards. The frequency of defecating bees was relatively low, and attempts were made to find “defecation triggers”. The bees were exposed to high and low temperature, to smoke, followed by centrifugation. It was concluded that centrifugation does affect bee survival negatively. Smoke combined with centrifugation showed a promising effect on defecation, and should be investigated further.